2010
DOI: 10.1634/theoncologist.2009-0213
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Cancer: Key Findings and Commentary on the Third Tegernsee Conference

Abstract: Cancer immunotherapy broadly includes active immunization, as in the use of cancer vaccines, passive immunization, such as the use of adoptive cell therapy and antibodies that modulate tumor function, and immunostimulation, using antibodies and small molecules to treat malignancy by activating or unleashing an endogenous immune response against tumor cells. Currently, >100 different monoclonal antibodies are in use or under evaluation for use as therapeutic agents in various malignancies. Active stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Treg numbers in the circulation of TLR2-deficient mice are reduced compared with their WT littermate controls [10] . Furthermore, the activation of the TLR2 signal may be crucial for tumor cells to escape killing by the host [29] . Huang et al recently found that activation of TLR2 on cancer cells by Listeria monocytogenes promotes tumor growth [30] , while Kim et al reported that activation of TLR2 by an extracellular matrix proteoglycan versican of Lewis lung carcinoma stimulates pro-tumor inflammation and metastasis [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treg numbers in the circulation of TLR2-deficient mice are reduced compared with their WT littermate controls [10] . Furthermore, the activation of the TLR2 signal may be crucial for tumor cells to escape killing by the host [29] . Huang et al recently found that activation of TLR2 on cancer cells by Listeria monocytogenes promotes tumor growth [30] , while Kim et al reported that activation of TLR2 by an extracellular matrix proteoglycan versican of Lewis lung carcinoma stimulates pro-tumor inflammation and metastasis [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that not only are there insufficient numbers of antitumor effector cells but that there are also too many immunosuppressive factors in tumor environment, which culminates in the failure to eradicate tumor cells [2,3] . Thus, a rational anti-cancer immunotherapeutic strategy should include both anti-tumor immune elements and elements able to eliminate tumor-induced immunosuppressive factors [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The tumor microenvironment represents a consistently effective barrier to clinical responses. 4 The need to design novel strategies based on targeting not only the tumor but also its microenvironment arises urgently.…”
mentioning
confidence: 99%
“…Available data support the hypothesis of an immune-mediated antitumor activity in breast carcinoma, and several lines of research are ongoing [90]. It is critical to understand what happens in the tumoral microenvironment in order to design biological agents that may modulate the immune response towards cancer cell destruction (Figure 2).…”
Section: Discussionmentioning
confidence: 99%